Utilization of the “Talking Bottle” as an Interactive Communication Medium to Improve the Communication Skills of Deaf Students in an Inclusive Campus - Bambang Yulianto; Sujarwanto S; Riki Nasrullah (Yayasan Daarul Huda Kruengmane, 2026)
Deaf students in higher education still face barriers in verbal communication that affect academic participation, social interaction, and self-confidence in various campus situations. This condition indicates the need for communication media that are more adaptive, practical, and easy to use in everyday interactions. This community service program aims to improve the communication skills of deaf students through the use of a “talking bottle” as an interactive communication medium in an inclusive campus environment. The program was implemented using a participatory approach, which included technical training on the use of the device, individual mentoring, communication simulations in real-life situations, and an inclusive communication awareness campaign at Universitas Negeri Surabaya. The results showed an increase in participants’ understanding of how the talking bottle works, the development of basic skills in forming simple utterances, increased confidence to participate in simulations and presentations, and the creation of more supportive interaction spaces through the assistance of facilitators, sign language interpreters, and supporting visual media.The program also demonstrates that strengthening communication skills among deaf students needs to be understood as a process involving technical, psychosocial, and campus social environment aspects. Therefore, the talking bottle can function as a relevant interactive communication medium to support the development of an inclusive campus, especially when accompanied by continuous training, operational modules, and support from the academic community.